Energy-absorbing buffer aluminum alloy material and preparation method thereof
Patent Information
- Application Number
- CN202410270696.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-03-11
AI Technical Summary
常规的铝合金能量吸收性差,减震效果也不行,后来研制出了泡沫铝合金,但是泡沫铝合金由于孔径大,孔隙率高,同时很多形成的是闭孔,因此,虽然减震效果不错,但是力学性能也相应的下降很多
[0023]本发明以纳米网膜和微米颗粒构建间隙,获得通孔的多孔铝合金,网膜所实现的特殊的通孔结构能够有效进行冲击能量的吸收、阻尼减震,起到了很好的减震缓冲效果。
Smart Images

Figure BDA0004734104060000071 
Figure BDA0004734104060000081
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of aluminum alloy materials, specifically to an energy-absorbing buffer aluminum alloy material and its preparation method. Background Technology
[0002] Aluminum is the second largest metal material in terms of production volume after steel. Due to its excellent performance, wide range of applications, large demand, and low recycling costs, it is known as the "universal metal." Statistics show that 113 out of 124 industries in my country use aluminum products, with an industrial linkage rate as high as 91%. Therefore, the aluminum industry is one of the important pillar raw material industries for the sustained development of the national economy. Conventional aluminum alloys have poor energy absorption and shock absorption effects. Later, foamed aluminum alloys were developed. However, due to their large pore size, high porosity, and the fact that many of them form closed pores, although the shock absorption effect is good, the mechanical properties are correspondingly reduced. Therefore, while meeting certain mechanical performance indicators, it is necessary to develop an aluminum alloy material with good shock absorption and cushioning effects. Summary of the Invention
[0003] Technical problem to be solved: In view of the above-mentioned technical problems, the purpose of this invention is to provide an energy-absorbing and buffering aluminum alloy material and its preparation method. The material uses a nano-mesh and micron-sized particles to construct gaps, thereby obtaining a porous aluminum alloy with through holes. The special through-hole structure achieved by the mesh can effectively absorb impact energy and dampen shock absorption, thus achieving a good shock absorption and buffering effect.
[0004] Technical solution: A method for preparing an energy-absorbing buffer aluminum alloy material, comprising the following steps:
[0005] Step 1: Lay a layer of nano-mesh in the mold;
[0006] Step 2: Lay another layer of micron-sized particle stack;
[0007] Step 3: Preheat the mold at 550℃ for 2 hours, and then infuse molten aluminum alloy at 720℃ into the gaps between the nanomesh and micron particles under a pressure of 20kPa.
[0008] Step 4: Cool to room temperature, remove the nanomesh and micron particles to obtain the energy-absorbing buffer aluminum alloy material.
[0009] Furthermore, the preparation method of the nanomembrane is as follows:
[0010] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and obtain an electrospinning solution;
[0011] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning and obtain an electrospinned membrane.
[0012] S3: Dry the electrospun film;
[0013] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0014] S5: Under N2 protection, the pre-oxidized mesh is carbonized to obtain the nanomembrane.
[0015] Furthermore, the mass ratio of the nano-calcium carbonate to PVP is (1-2):2.
[0016] Furthermore, the electrospinning conditions are as follows: spinning voltage is 15kV, spinning solution flow rate is 0.3-0.5mL / h, and receiving distance is 15cm.
[0017] Furthermore, the carbonization conditions are as follows: N2 flow rate of 15 mL / s, heating rate of 1 °C / min, and holding at 700 °C for 1 h.
[0018] Furthermore, the micron-sized particles are NaCl particles.
[0019] Furthermore, the NaCl particles have a particle size of 1.0-2.0 mm.
[0020] Furthermore, the composition of the aluminum alloy melt is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al.
[0021] The energy-absorbing buffer aluminum alloy material prepared by the above preparation method.
[0022] Beneficial effects:
[0023] This invention uses nanofiber mesh and micron particles to construct gaps, thereby obtaining a porous aluminum alloy with through holes. The special through-hole structure achieved by the mesh can effectively absorb impact energy and dampen vibration, thus achieving a good shock absorption and buffering effect. Detailed Implementation
[0024] This invention proposes an energy-absorbing buffer aluminum alloy material and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following will provide a more detailed description of the invention in conjunction with embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0025] Example 1
[0026] A method for preparing an energy-absorbing buffer aluminum alloy material includes the following steps:
[0027] Step 1: Lay a layer of nano-mesh in the mold;
[0028] Step 2: Lay another layer of NaCl particle stack with a particle size of 1.0-2.0 mm; the volume ratio of NaCl particle stack to nanomembrane is 1:3;
[0029] Step 3: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps constructed by the nano-mesh and micron particles under a pressure of 20 kPa; the composition of the molten aluminum alloy is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al;
[0030] Step 4: Cool to room temperature, immerse in dilute hydrochloric acid, and ultrasonically vibrate to remove the nano-mesh and micron particles, thus obtaining the energy-absorbing buffer aluminum alloy material.
[0031] The preparation method of the nanomembrane is as follows:
[0032] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and the mass ratio of nano-calcium carbonate to PVP is 1:2 to obtain an electrospinning solution;
[0033] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning. The electrospinning conditions are: spinning voltage of 15kV, spinning solution flow rate of 0.4mL / h, and receiving distance of 15cm to obtain an electrospinned membrane.
[0034] S3: Dry the electrospun film;
[0035] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0036] S5: Under N2 protection, the pre-oxidized membrane is carbonized. The carbonization conditions are: N2 flow rate of 15 mL / s, heating rate of 1℃ / min, and constant temperature at 700℃ for 1 h to obtain the nanomembrane.
[0037] Example 2
[0038] A method for preparing an energy-absorbing buffer aluminum alloy material includes the following steps:
[0039] Step 1: Lay a layer of nano-mesh in the mold;
[0040] Step 2: Lay another layer of NaCl particle stack with a particle size of 1.0-2.0 mm; the volume ratio of NaCl particle stack to nanomembrane is 1:4;
[0041] Step 3: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps constructed by the nano-mesh and micron particles under a pressure of 20 kPa; the composition of the molten aluminum alloy is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al;
[0042] Step 4: Cool to room temperature, immerse in dilute hydrochloric acid, and ultrasonically vibrate to remove the nano-mesh and micron particles, thus obtaining the energy-absorbing buffer aluminum alloy material.
[0043] The preparation method of the nanomembrane is as follows:
[0044] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and the mass ratio of nano-calcium carbonate to PVP is 1:2 to obtain an electrospinning solution;
[0045] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning. The electrospinning conditions are: spinning voltage of 15kV, spinning solution flow rate of 0.4mL / h, and receiving distance of 15cm to obtain an electrospinned membrane.
[0046] S3: Dry the electrospun film;
[0047] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0048] S5: Under N2 protection, the pre-oxidized membrane is carbonized. The carbonization conditions are: N2 flow rate of 15 mL / s, heating rate of 1℃ / min, and constant temperature at 700℃ for 1 h to obtain the nanomembrane.
[0049] Example 3
[0050] A method for preparing an energy-absorbing buffer aluminum alloy material includes the following steps:
[0051] Step 1: Lay a layer of nano-mesh in the mold;
[0052] Step 2: Lay another layer of NaCl particle stack with a particle size of 1.0-2.0 mm; the volume ratio of NaCl particle stack to nanomembrane is 1:5;
[0053] Step 3: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps constructed by the nano-mesh and micron particles under a pressure of 20 kPa; the composition of the molten aluminum alloy is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al;
[0054] Step 4: Cool to room temperature, immerse in dilute hydrochloric acid, and ultrasonically vibrate to remove the nano-mesh and micron particles, thus obtaining the energy-absorbing buffer aluminum alloy material.
[0055] The preparation method of the nanomembrane is as follows:
[0056] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and the mass ratio of nano-calcium carbonate to PVP is 1:2 to obtain an electrospinning solution;
[0057] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning. The electrospinning conditions are: spinning voltage of 15kV, spinning solution flow rate of 0.4mL / h, and receiving distance of 15cm to obtain an electrospinned membrane.
[0058] S3: Dry the electrospun film;
[0059] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0060] S5: Under N2 protection, the pre-oxidized membrane is carbonized. The carbonization conditions are: N2 flow rate of 15 mL / s, heating rate of 1℃ / min, and constant temperature at 700℃ for 1 h to obtain the nanomembrane.
[0061] Example 4
[0062] A method for preparing an energy-absorbing buffer aluminum alloy material includes the following steps:
[0063] Step 1: Lay a layer of nano-mesh in the mold;
[0064] Step 2: Lay another layer of NaCl particle stack with a particle size of 1.0-2.0 mm; the volume ratio of NaCl particle stack to nanomembrane is 1:4;
[0065] Step 3: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps constructed by the nano-mesh and micron particles under a pressure of 20 kPa; the composition of the molten aluminum alloy is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al;
[0066] Step 4: Cool to room temperature, immerse in dilute hydrochloric acid, and ultrasonically vibrate to remove the nano-mesh and micron particles, thus obtaining the energy-absorbing buffer aluminum alloy material.
[0067] The preparation method of the nanomembrane is as follows:
[0068] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and the mass ratio of nano-calcium carbonate to PVP is 2:2 to obtain an electrospinning solution;
[0069] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning. The electrospinning conditions are: spinning voltage of 15kV, spinning solution flow rate of 0.4mL / h, and receiving distance of 15cm to obtain an electrospinned membrane.
[0070] S3: Dry the electrospun film;
[0071] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0072] S5: Under N2 protection, the pre-oxidized membrane is carbonized. The carbonization conditions are: N2 flow rate of 15 mL / s, heating rate of 1℃ / min, and constant temperature at 700℃ for 1 h to obtain the nanomembrane.
[0073] Example 5
[0074] A method for preparing an energy-absorbing buffer aluminum alloy material includes the following steps:
[0075] Step 1: Lay a layer of nano-mesh in the mold;
[0076] Step 2: Lay another layer of NaCl particle stack with a particle size of 1.0-2.0 mm; the volume ratio of NaCl particle stack to nanomembrane is 1:4;
[0077] Step 3: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps constructed by the nano-mesh and micron particles under a pressure of 20 kPa; the composition of the molten aluminum alloy is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al;
[0078] Step 4: Cool to room temperature, immerse in dilute hydrochloric acid, and ultrasonically vibrate to remove the nano-mesh and micron particles, thus obtaining the energy-absorbing buffer aluminum alloy material.
[0079] The preparation method of the nanomembrane is as follows:
[0080] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and the mass ratio of nano-calcium carbonate to PVP is 1:2 to obtain an electrospinning solution;
[0081] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning. The electrospinning conditions are: spinning voltage of 15kV, spinning solution flow rate of 0.3mL / h, and receiving distance of 15cm to obtain an electrospinned membrane.
[0082] S3: Dry the electrospun film;
[0083] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0084] S5: Under N2 protection, the pre-oxidized membrane is carbonized. The carbonization conditions are: N2 flow rate of 15 mL / s, heating rate of 1℃ / min, and constant temperature at 700℃ for 1 h to obtain the nanomembrane.
[0085] Example 6
[0086] A method for preparing an energy-absorbing buffer aluminum alloy material includes the following steps:
[0087] Step 1: Lay a layer of nano-mesh in the mold;
[0088] Step 2: Lay another layer of NaCl particle stack with a particle size of 1.0-2.0 mm; the volume ratio of NaCl particle stack to nanomembrane is 1:4;
[0089] Step 3: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps constructed by the nano-mesh and micron particles under a pressure of 20 kPa; the composition of the molten aluminum alloy is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al;
[0090] Step 4: Cool to room temperature, immerse in dilute hydrochloric acid, and ultrasonically vibrate to remove the nano-mesh and micron particles, thus obtaining the energy-absorbing buffer aluminum alloy material.
[0091] The preparation method of the nanomembrane is as follows:
[0092] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and the mass ratio of nano-calcium carbonate to PVP is 1:2 to obtain an electrospinning solution;
[0093] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning. The electrospinning conditions are: spinning voltage of 15kV, spinning solution flow rate of 0.5mL / h, and receiving distance of 15cm to obtain an electrospinned membrane.
[0094] S3: Dry the electrospun film;
[0095] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0096] S5: Under N2 protection, the pre-oxidized membrane is carbonized. The carbonization conditions are: N2 flow rate of 15 mL / s, heating rate of 1℃ / min, and constant temperature at 700℃ for 1 h to obtain the nanomembrane.
[0097] Comparative Example 1
[0098] The difference between this embodiment and Embodiment 2 is that a nanomembrane is not laid; instead, a NaCl particle stack is used. The total volume of the nanomembrane and the NaCl particle stack is the same as in Embodiment 2. Specifically:
[0099] A method for preparing an energy-absorbing buffer aluminum alloy material includes the following steps:
[0100] Step 1: Lay a layer of NaCl particles with a particle size of 1.0-2.0 mm;
[0101] Step 2: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps constructed by the nano-mesh and micron particles under a pressure of 20 kPa; the composition of the molten aluminum alloy is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al;
[0102] Step 3: Cool to room temperature, immerse in dilute hydrochloric acid, and ultrasonically vibrate to remove the nano-mesh and micron particles, thus obtaining the energy-absorbing buffer aluminum alloy material.
[0103] The preparation method of the nanomembrane is as follows:
[0104] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and the mass ratio of nano-calcium carbonate to PVP is 1:2 to obtain an electrospinning solution;
[0105] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning. The electrospinning conditions are: spinning voltage of 15kV, spinning solution flow rate of 0.4mL / h, and receiving distance of 15cm to obtain an electrospinned membrane.
[0106] S3: Dry the electrospun film;
[0107] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0108] S5: Under N2 protection, the pre-oxidized membrane is carbonized. The carbonization conditions are: N2 flow rate of 15 mL / s, heating rate of 1℃ / min, and constant temperature at 700℃ for 1 h to obtain the nanomembrane.
[0109] Comparative Example 2
[0110] The difference between this embodiment and Embodiment 2 is that no NaCl particle packing is laid out. Specifically:
[0111] A method for preparing an energy-absorbing buffer aluminum alloy material includes the following steps:
[0112] Step 1: Lay a layer of nano-mesh in the mold;
[0113] Step 2: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps constructed by the nano-mesh and micron particles under a pressure of 20 kPa; the composition of the molten aluminum alloy is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al;
[0114] Step 3: Cool to room temperature, immerse in dilute hydrochloric acid, and ultrasonically vibrate to remove the nano-mesh and micron particles, thus obtaining the energy-absorbing buffer aluminum alloy material.
[0115] The preparation method of the nanomembrane is as follows:
[0116] S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and the mass ratio of nano-calcium carbonate to PVP is 1:2 to obtain an electrospinning solution;
[0117] S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning. The electrospinning conditions are: spinning voltage of 15kV, spinning solution flow rate of 0.4mL / h, and receiving distance of 15cm to obtain an electrospinned membrane.
[0118] S3: Dry the electrospun film;
[0119] S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh.
[0120] S5: Under N2 protection, the pre-oxidized membrane is carbonized. The carbonization conditions are: N2 flow rate of 15 mL / s, heating rate of 1℃ / min, and constant temperature at 700℃ for 1 h to obtain the nanomembrane.
[0121] According to the national standard GB / T16865-2013, the energy-absorbing buffer aluminum alloy materials of each embodiment were processed into standard tensile specimens. The mechanical properties were determined using a CMT5105 electronic universal testing machine. Three sets of data were measured for each sample, and the average value was taken. The mechanical properties are shown in Table 1.
[0122] Table 1
[0123]
[0124]
Claims
1. A method for preparing an energy-absorbing buffer aluminum alloy material, characterized in that, Includes the following steps: Step 1: Lay a layer of nano-mesh in the mold; Step 2: Lay another layer of NaCl particles with a particle size of 1.0-2.0 mm; Step 3: Preheat the mold at 550℃ for 2 hours, and then infiltrate the molten aluminum alloy at 720℃ into the gaps between the nanomesh and NaCl particles under a pressure of 20 kPa. Step 4: Cool to room temperature, remove the nanomembrane and NaCl particles to obtain the energy-absorbing buffer aluminum alloy material; The method for preparing the nanomembrane is as follows: S1: Prepare a PVP ethanol solution with a mass fraction of 8 wt.%, add nano-calcium carbonate, and obtain an electrospinning solution; S2: Inject the electrospinning solution into the syringe of the electrospinning device to perform electrospinning and obtain an electrospinned membrane. S3: Dry the electrospun film; S4: Place it in a sintering furnace, heat it to 200℃, and then heat it to 250℃ within 1 hour and keep it at that temperature for 1 hour for pre-oxidation to obtain a pre-oxidized mesh. S5: Under N2 protection, the pre-oxidized mesh is carbonized to obtain the nanomembrane; The mass ratio of the nano-calcium carbonate to PVP is (1-2):2; The volume ratio of NaCl particle packing to nanomembrane is 1:3, 1:4, or 1:
5.
2. The method for preparing an energy-absorbing buffer aluminum alloy material according to claim 1, characterized in that, The electrospinning conditions are as follows: spinning voltage is 15 kV, spinning solution flow rate is 0.3-0.5 mL / h, and receiving distance is 15 cm.
3. The method for preparing an energy-absorbing buffer aluminum alloy material according to claim 1, characterized in that, The carbonization conditions were as follows: N2 flow rate of 15 mL / s, heating rate of 1 °C / min, and constant temperature for 1 h after heating to 700 °C.
4. The method for preparing an energy-absorbing buffer aluminum alloy material according to claim 1, characterized in that, The composition of the aluminum alloy melt is: 3.6 wt.% Si, 1.2 wt.% Cu, 0.4 wt.% Mg, 0.5 wt.% Zn, with the balance being Al.
5. The energy-absorbing buffer aluminum alloy material prepared by the method for preparing an energy-absorbing buffer aluminum alloy material according to any one of claims 1-4.
Citation Information
Patent Citations
Porous aluminum alloy with micron-stage pore and preparation method thereof
CN101260490A
Porous carbon nano fiber material for adsorbing carbon dioxide and preparation method thereof
CN107051382A
